(untitled) - Snelling, Lauraine; Giron, Kiersti (Minneapolis, Minnesota, 2025)
"Norwegian immigrant Amalia Gunderson and her ward, Ruth Forsberg, arrive in Iowa to claim the boardinghouse Ruth has inherited, despite opposition from a difficult cousin. While Amalia looks for her long-lost brother, her relationship with an attorney unfolds as she and Ruth navigate through love, loss, and unexpected friendships"--
Keywords: Orphans; Fiction; Inheritance and succession; Care; Fiction; Fiction; Fiction; Man-woman relationships; United States; Fiction; Women imigrants; Boardinghouses; Iowa; Fiction; Christian fiction; Romance fiction; Historical fiction; Novels